Mobile Phones Technolgy for Memorising the Qur’an: An Islamic Student Perspective - Nuruddin Nuruddin (UIN Mataram, 2023)
The proliferation of digital information is a pressing need that requires effective skills for all individuals, including university students. Easy access to various social media platforms has enabled the formation of friendship networks involving individuals from all over the world, which often leads to over-involvement and neglect of other activities. This study is a descriptive study that aims to describe the activities of students who memorise the Qur'an. The data collection method used was a questionnaire, while data analysis was conducted using a descriptive data analysis approach. The study results revealed that students who memorise the Qur'an more frequently access social media applications, with YouTube being the most accessed platform. Some of the obstacles that students face in the process of memorising the Qur'an involve factors such as laziness and boredom, weak memory, inconsistency, romantic distractions, difficulties in time management, influence from friends, busyness in organisations, and the influence of mobile phone use. In addition, social media applications such as YouTube, Instagram, and TikTok were identified as factors inhibiting the Qur’anic memorisation process. Abstrak: Perkembangan informasi digital menjadi kebutuhan mendesak yang memerlukan kemampuan efektif bagi semua individu, termasuk mahasiswa. Akses yang mudah ke berbagai platform media sosial telah memungkinkan terbentuknya jaringan pertemanan yang melibatkan individu dari seluruh dunia, yang sering kali menyebabkan keterlibatan yang berlebihan dan pengabaian terhadap aktivitas lain. Penelitian ini merupakan penelitian deskriptif yang bertujuan untuk menggambarkan aktivitas mahasiswa penghafal Al-Qur'an. Metode pengumpulan data yang digunakan adalah kuesioner, sementara analisis data dilakukan dengan menggunakan pendekatan analisis data deskriptif. Hasil studi mengungkapkan bahwa mahasiswa penghafal Al-Qur'an lebih sering mengakses aplikasi media sosial, dengan YouTube menjadi platform yang paling banyak diakses. Beberapa hambatan yang dihadapi mahasiswa dalam proses menghafal Al-Qur'an melibatkan faktor-faktor seperti rasa malas dan bosan, daya ingat yang lemah, ketidakkonsistenan, gangguan asmara, kesulitan dalam manajemen waktu, pengaruh dari teman-teman, kesibukan dalam organisasi, dan pengaruh penggunaan ponsel. Selain itu, aplikasi media sosial seperti YouTube, Instagram, dan TikTok diidentifikasi sebagai faktor penghambat proses menghafal Al-Qur'an.